2006
DOI: 10.1021/bi0615902
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility and Strand Arrangements of the Membrane-Associated HIV Fusion Peptide Trimer Probed by Solid-State NMR Spectroscopy

Abstract: The human immunodeficiency virus (HIV) fusion peptide (HFP) is the N-terminal apolar region of the HIV gp41 fusion protein and interacts with target cell membranes and promotes membrane fusion. The free peptide catalyzes vesicle fusion at least to the lipid mixing stage and serves as a useful model fusion system. For gp41 constructs which lack the HFP, high-resolution structures show trimeric protein and suggest that at least three HFPs interact with the membrane with their C-termini in close proximity. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
124
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(139 citation statements)
references
References 113 publications
(434 reference statements)
12
124
1
Order By: Relevance
“…For the HFP3-8 FLG and HFP2-14 AAG samples associated with PC:PG, there were shoulders at ~178 and 179 ppm, respectively, which correlated with helical conformation of Ala, Leu, and Phe residues. These results were consistent with previous studies of the conformation of membrane-associated HFP with peptide:lipid ~ 0.04 and with previous observations of greater preference for β strand conformation in cholesterol-containing membranes (27,28,35,55,56,59,70). The data demonstrated that samples containing HFP2-14 AAG have qualitatively larger (ΔS/ S 0 ) exp than do samples containing HFP labeled at other residues.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 92%
See 4 more Smart Citations
“…For the HFP3-8 FLG and HFP2-14 AAG samples associated with PC:PG, there were shoulders at ~178 and 179 ppm, respectively, which correlated with helical conformation of Ala, Leu, and Phe residues. These results were consistent with previous studies of the conformation of membrane-associated HFP with peptide:lipid ~ 0.04 and with previous observations of greater preference for β strand conformation in cholesterol-containing membranes (27,28,35,55,56,59,70). The data demonstrated that samples containing HFP2-14 AAG have qualitatively larger (ΔS/ S 0 ) exp than do samples containing HFP labeled at other residues.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 92%
“…This result correlated with previous studies which supported the following structural features: (1) β strand HFP was fully extended between A1 and G16; (2) β strand HFP formed hydrogen bonded oligomers or aggregates; and (3) a significant fraction of the oligomers have an antiparallel arrangement with adjacent strand crossing between F8 and L9 (25,(27)(28)(29)35,37,85,86). Some of these studies also supported conformational disorder at A21 (27,28).…”
Section: Insertion Modelssupporting
confidence: 89%
See 3 more Smart Citations